Socioeconomic Outcome of Ecological Restoration Project: A Case Study of Ex-Oil and Gas Mining Areas - Lubis, Abdillah; Nurhayati, Nurhayati; Anwar, Syaiful (PT. Pubsains Nur Cendekia, 2025)
Ecological restoration in former oil and gas extraction sites plays a vital role in promoting sustainable development. This study examines the socio-economic impacts of community-based ecological restoration efforts in Riau Province. This research used a qualitative case study design with purposive sampling. Data were obtained through observation, interviews, and document analysis, then analyzed inductively to identify emerging patterns. The findings reveal that the revegetation program of PT Pertamina Hulu Rokan generated tangible benefits by employing 302 local workers and reducing conflicts through Local Business Development. A financial commitment of USD 1.4 million to local enterprises reflects the synergy between corporate environmental responsibility and community economic growth. The study underscores the importance of integrating corporate environmental initiatives with local economic strategies to foster sustainable development and enhance community well-being in post-extraction landscapes.